The Parable of The Lame and The Blind In Epiphanius and its Relation to Jewish Sources New Texts - Mints-Manor, Ofir (2017)
This essay discusses recently discovered Hebrew liturgical poems from late antique Palestine that shed new light on a passage in the Panarion where Epiphanius discusses the relationship between body and soul and presents a parable on a lame and a blind person. Epiphanius’ version of the parable has drawn the attention of scholars because of its likeness to rabbinic texts. Some 25 years ago Marc Bregman dedicated an article in the Journal of Theological Studies to the examination of Epiphanius’ versions vis-à-vis rabbinic traditions and offered some ingenious conclusions concerning the relationship between Christian and Jewish texts from Late Antiquity. The new poetic texts shed fresh light on Bregman’s conclusions, corroborating some of his assertions while casting doubt on others. In addition, the examination of the liturgical poems reveals the rich dynamics between prose and verse in contemporary Jewish literature. Finally, the essay singles out the importance of the study of late antique liturgical poetry in treatments of rabbinic and patristic writings.